Current issues and future considerations for the wider implementation of robotic-assisted surgery: a qualitative study. Issue 11 (11th November 2022) - Lawrie, Louisa; Gillies, Katie; Davies, Loretta; Torkington, Jared; McGrath, John; Kerr, Richard; Immanuel, Arul; Campbell, Marion; Beard, David
Abstract : Objectives: The effective implementation of a fast-changing healthcare delivery innovation, such as robotic-assisted surgery (RAS), into a healthcare system, can be affected (both positively and negatively) by external contextual factors. As part of a wider project investigating ways to optimise the implementation of RAS, this qualitative study aimed to uncover current issues of RAS and predictions about the future of robotic surgery. We refer to 'current issues' as the topical and salient challenges and opportunities related to the introduction of RAS in the UK healthcare system, from the perspectives of key stakeholders involved in the delivery and implementation of RAS. Design: Semi-structured interviews and focus groups were conducted. A thematic analysis was conducted to summarise salient issues that were articulated by the participants. Setting and participants: The interview sample (n=35) comprised surgeons, wider theatre staff and other relevant personnel involved in the introduction and delivery of RAS services across the UK, including service managers and policymakers/commissioners. Two focus groups were also conducted with surgical trainees (n=7) and members of the public (n=8), respectively. Results: The results revealed a largely positive attitude towards the introduction of RAS technology and an expectation of continued rapid expansion. Areas perceived to be particularly pertinent and requiring ongoing attention were also highlighted, including the need to achieve improved quality control, expertise quantification and training issues and the need to educate the public. Issues of centralisation, service organisation and equity of access were also emphasised. Conclusions: Our study has highlighted a range of issues perceived to be particularly pertinent to the current and future provision of RAS which should be addressed. The areas outlined can enable healthcare managers and surgeons to plan for the adoption and/or expansion of RAS services.